Parental digital health information seeking behavior in Switzerland: a cross-sectional study - Rebecca Jaks; Isabel Baumann; Sibylle Juvalta; Julia Dratva (BMC, 2019)
Abstract Background Digital media are increasingly abundant and used to seek health information, however, to date very little is known on parents' seeking behavior in the context of child's health and development outside English-speaking and Scandinavian countries. By investigating the prevalence of, and reasons for use, we studied parents' perception of the Internet as a resource for improving their health-related knowledge. Methods The survey was conducted in a random sample of 2573 Swiss-German parents with at least one child aged less-than 2 years old. Parents received a mailed invitation to fill in an online questionnaire. Two reminders were sent, the later with a paper questionnaire attached. The questionnaire included questions on use of print, digital, and personal information sources, as well as different information situations: general health and development or illness. We ran descriptive analyses on information seeking behavior, type of digital media used, reasons of use. We also conducted regression analyses to explore factors associated with parental perceptions with regard to the Internet's utility as a source for health information. Results A total of 769 questionnaires were returned (response rate 30%). Nearly all parents (91%) used digital media for seeking information on their child's health and development, and the main reason for use was indicated as being the 24/7 availability of information. Search engines (55%) and webpages for parents (47%) were by far the most frequently used digital media. Generally, the internet is perceived as a good resource, especially by fathers (OR = 1.80, 95% CI: 1.03-3.16). However, a large percentage of parents are skeptical about the correctness of online info (91%), are unsure about their interpretive understanding, and ask for guidance from their pediatrician (67%). Conclusions The Internet has become a highly frequented source of information for Swiss-German parents on children's health with largely valuable perceptions of its utility. Digital media are used in addition to and not in replacement of print media and personal contacts. Increasing parental guidance by health and public health professionals could improve parental digital health utilization and empower parents in the new role they adopt.